The globally widespread genus Sulfurimonas: versatile energy metabolisms and adaptations to redox clines - Han, Yuchen; Perner, Mirjam (Frontiers in Microbiology, 2015)
Sulfurimonas species are commonly isolated from sulfidic habitats and numerous 16S rRNA sequences related to Sulfurimonas species have been identified in chemically distinct environments, such as hydrothermal deep-sea vents, marine sediments, the ocean’s water column, and terrestrial habitats. In some of these habitats, Sulfurimonas have been demonstrated to play an important role in chemoautotrophic processes. Sulfurimonas species can grow with a variety of electron donors and acceptors, which may contribute to their widespread distribution. Multiple copies of one type of enzyme (e.g., sulfide:quinone reductases and hydrogenases) may play a pivotal role in Sulfurimonas’ flexibility to colonize disparate environments. Many of these genes appear to have been acquired through horizontal gene transfer which has promoted adaptations to the distinct habitats. Here we summarize Sulfurimonas’ versatile energy metabolisms and link their physiological properties to their global distribution.